Bilateral Renal Tumour as Indicator for Birt-Hogg-Dubé Syndrome - P. C. Johannesma; R. J. A. van Moorselaar; S. Horenblas; L. E. van der Kolk; E. Thunnissen; J. H. T. M. van Waesberghe; F. H. Menko; P. E. Postmus (Case Reports in Medicine)
Birt-Hogg-Dubé (BHD) syndrome is a cancer disorder caused by a pathogenic FLCN mutation characterized by fibrofolliculomas, lung cysts, pneumothorax, benign renal cyst, and renal cell carcinoma (RCC). In this case we describe a patient with bilateral renal tumour and a positive familial history for pneumothorax and renal cancer. Based on this clinical presentation, the patient was suspected for BHD syndrome, which was confirmed after molecular testing. We discuss the importance of recognizing this autosomal dominant cancer disorder when a patient is presented at the urologist with a positive family history of chromophobe renal cell cancer or a positive familial history for renal cell cancer and pneumothorax.